Neo-Baroque A Sign of the Times - Calabrese, Omar (Princeton Legacy Library, 2017)
These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905